WORKPLACE HEALTH PROMOTION ACTIONS IN COMPANIES: AN INTERDISCIPLINARY CONTRIBUTION - Daniela Inês Thier Roloff; Marlise Capa Verde Almeida de Mello; Clarice Alves Bonow; Marta Regina Cezar-Vaz (Universidade Federal do Paraná, 2019)
Objective: To analyze the health promotion actions of Specialized Services of Work Safety Engineering and Occupational Medicine from companies and the health promotion actions of companies in their official websites.Method: Qualitative, exploratory and descriptive study with 34 occupational health and safety professionals from seven companies in southern Brazil. The interviews were conducted in 2015 and documentary research was performed in 2016 for Content Analysis.Results: Two categories of analysis were constructed and named "Health promotion activities: professionals' report" and "Health promotion activities: public communication of companies".Final considerations: Health promotion actions are implemented by companies. The actions carried out by health and safety professionals are targeted to workers and the work environment, and the actions disseminated by the companies are focused on integrated management of the work process, personal development, environmental, social and economic responsibilities.